Pengaruh Pembelajaran Kooperatif Berbasis Teori Van Hiele Terhadap Kemampuan Pemecahan Masalah Geometri Mahasiswa Pendidikan Matematika - Hera Deswita; Nurrahmawati (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2019)
One of the mathematical problems whose solution requires the problem solving ability is geometry. Van Hiele's Theory is a learning solution that can be applied to practice the problem solving ability of geometry. Van Hiele states that the 5 levels of geometry thinking are the stages of introduction, analysis, sequencing, deduction and accuracy. The purpose of this study was to determine whether or not the influence of Van Hiele's theory-based cooperative learning on the geometrical problem solving abilities of students of Mathematics Education at Pasir Pengaraian University on space geometry. This study uses a quasi-experimental method with the design of Two Group Posttest Only. The population in this study were students of mathematics education at the Pasir Pengaraian University. The technique used for sampling is saturated samples, namely fifth semester students taking three-dimentional geometry. The instrument used was a test of problem solving ability. Data analysis using t-test. The results showed that the acquisition value of sig 0.001 <0.05. Thus it can be concluded that there is an influence of Van Hiele's theory-based cooperative learning on the ability of problem solving geometry of students of Mathematics Education at Pasir Pengaraian University on space geometry.